1995
DOI: 10.1007/bf00294688
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that two zinc fingers in the methionine aminopeptidase from Saccharomyces cerevisiae are important for normal growth

Abstract: Limited proteolysis of intact yeast methionine aminopeptidase (MAP1) with trypsin releases a 34 kDa fragment whose NH2-terminal sequence begins at Asp70, immediately following Lys69. These results suggest that yeast MAP may have a two-domain structure consisting of an NH2-terminal zinc finger domain and a C-terminal catalytic domain. To test this, a mutant MAP lacking residues 2-69 was generated, overexpressed, purified and analyzed. Metal ion analyses indicate that 1 mol of wild-type yeast MAP contains 2 mol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 53 publications
3
54
1
Order By: Relevance
“…We recently showed that the zinc fingers of yeast Met-AP1 are essential for normal Met-AP1 function in vivo, even though they are not involved in catalysis in vitro. These findings support the hypothesis that the zinc fingers may act as a binding domain linking Met-AP1 to a site near the exit of the nascent polypeptides that facilitate its processing function in vivo (21). Similarly, the rat p67 has been shown to be associated with eIF-2, which carries the initiator methionine to the ribosomes.…”
Section: Ggccacagtatcgcaccatatcgtatccacggcggtaaatccgttccc G H S I a Psupporting
confidence: 75%
“…We recently showed that the zinc fingers of yeast Met-AP1 are essential for normal Met-AP1 function in vivo, even though they are not involved in catalysis in vitro. These findings support the hypothesis that the zinc fingers may act as a binding domain linking Met-AP1 to a site near the exit of the nascent polypeptides that facilitate its processing function in vivo (21). Similarly, the rat p67 has been shown to be associated with eIF-2, which carries the initiator methionine to the ribosomes.…”
Section: Ggccacagtatcgcaccatatcgtatccacggcggtaaatccgttccc G H S I a Psupporting
confidence: 75%
“…Experimental results imply that the inhibition of MetAP peptidase activity disrupts the intricate balance between positive and negative regulators of angiogenesis (29,30). Although these compounds have been used primarily in cancer therapy, they also may be effective in noncancerous diseases of aberrant vascularization (29,30) and the treatment of pathogenic microorganisms, including E. coli (31)(32)(33)(34) and microsporidia in AIDS patients (35).…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal sequence of the yeast MetAP has two putative zinc-finger domains that may allow interactions with nucleic acid (13). The excision of these domains has little effect on the catalytic properties of the enzyme, but the construct expressing this truncated form is significantly less effective in rescuing the slow-growth phenotype of a MetAP mutant as compared with the wild-type MetAP (34). In contrast, the human enzyme lacks the consensus zinc-finger sequences and instead contains the extended runs of basic and acidic residues.…”
Section: Discussionmentioning
confidence: 99%